Convention consulaire conclue entre la Turquie et l'Autriche-Hongrie en date du 26 février/15 avril 1909 (Imprimerie Hilal, 1909)
Treaty signed between the Ottoman and Austro-Hungarian Empires settling the political statuses of Bosnia-Herzegovina and Novi Pazar.